Produção de lacases pelo fungo filamentoso de origem marinha Peniophora sp. CBMAI 1063 em biorreator de bancada - Mainardi, Pedro Henrique [UNESP] (2015)
Laccases are enzymes that catalyzes a reaction that oxidizes phenolic compounds. With a great biotechnological potential, laccases can be applied in many industrial areas. Most of the applications are related to pulp and paper, textile, food and beverage industries, as well as in synthetic chemistry and bioremediation. In earlier studies, the basidiomycete Peniophora sp. CBMAI 1063, isolated from marine sponge Amphimedon viridis, exhibited 1.350 U/L of laccases' activity under submerged culture in optimized saline medium. Taking into consideration the importance of the fungi and these enzymes for biotechnology, the purpose of this work was to study the laccases' production by the marine-derived basidiomycete Peniophora sp. CBMAI 1063 in bench bioreactors. It was performed 11 experiments in stirred tank reactor (STR) and one in pneumatic bioreactor (air-lift), establishing parameters such as inoculum incubation time, frequency of agitation, kLa, and initial pH value. The maximum laccases activity obtained in stirred tank reactor was 2.700 U/L in 120 hours of cultivation under 150 rpm of agitation (1,0 vvm: kLa de 17.2 h-1) and initial pH value of 4.5. In those conditions, with the inoculum cultivated for 120 hours, the maximum product formation rate was 60 U/L.h and the maximum productivity was 25.5 U/L.h. The fungus when cultivated in air-lift bioreactor under 1.0 vvm of aeration showed the activity of 4.014 U/L in 96 hours of growth. The maximum product formation rate obtained in that experiment was 55 U/L.h and the maximum productivity was 40 U/L.h. Analysis of the macro-morphology at the end of the processes indicated that STR bioreactor caused more damage to the fungus' mycelium than the air-lift bioreactor. Additional experiments in agitated flasks showed that the fungi Peniophora sp. CBMAI 1063 had higher laccases' activity and higher yields of dry biomass in the presence of 65% (v/v) of artificial seawater (ASW) and 2mM of ...